2011
DOI: 10.1029/2010wr009797
|View full text |Cite
|
Sign up to set email alerts
|

Comparative hydrology across AmeriFlux sites: The variable roles of climate, vegetation, and groundwater

Abstract: [1] Watersheds can be characterized as complex space-time filters that transform incoming fluxes of energy, water, and nutrients into variable output signals. The behavior of these filters is driven by climate, geomorphology, and ecology and, accordingly, varies from site to site. We investigated this variation by exploring the behavior of evapotranspiration signals from 14 different AmeriFlux sites. Evapotranspiration is driven by water and energetic forcing and is mediated by ecology and internal redistribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 71 publications
3
83
0
1
Order By: Relevance
“…Strategically, many existing observation networks could be leveraged to generate valuable data sets for interdisciplinary hydrology (see Table 2). For instance, the Fluxnet data sets provide unrivalled, high resolution information about evapo-transpiration dynamics, but insufficient soil moisture observations to allow water budget closure (Thompson et al, 2011b). Adding these soil moisture observations would increase the hydrologic value of these sites at a relatively small cost, compared to the costs of the eddy-covariance instrumentation already present.…”
Section: Collaborating To Share Data and Make Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategically, many existing observation networks could be leveraged to generate valuable data sets for interdisciplinary hydrology (see Table 2). For instance, the Fluxnet data sets provide unrivalled, high resolution information about evapo-transpiration dynamics, but insufficient soil moisture observations to allow water budget closure (Thompson et al, 2011b). Adding these soil moisture observations would increase the hydrologic value of these sites at a relatively small cost, compared to the costs of the eddy-covariance instrumentation already present.…”
Section: Collaborating To Share Data and Make Observationsmentioning
confidence: 99%
“…Comparative hydrology supersedes case study or watershed-specific approaches to hydrologic research, and has the potential to separate sitespecific phenomena from generalizable trends (Falkenmark and Chapman, 1989;McDonnell et al, 2007). With information about hydrological behavior in a large number of watersheds, robust testing of hypotheses generated from comprehensive investigations of a small number of sites (Thompson et al, 2011b) can be generalized via the statistical power of a large data set. Alternatively, statistical and top-down modeling approaches (Sivapalan et al, 2003) applied to many watersheds can be used to identify and explore emergent patterns (Voepel et al, 2011), which can then become targets of hypothesis formation and mechanistic inquiry.…”
Section: Comparative Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson et al (2011) and Ye et al (2012) showed that not accounting for vegetation phenology can lead to poor predictions of both seasonal evaporation and runoff variability in the northeastern USA, and that a temperature correction that mimics the phenology can help to improve the predictions. More globally, Cayan et al (2001) showed that in areas of the world with significant deciduous forests, changes in transpiration associated with phenology can contribute to significant changes in seasonal runoff.…”
Section: H Liu Et Al: Soil Moisture Controls On Patterns Of Grass Gmentioning
confidence: 99%
“…These processes, and their interactions with changes to canopy structure and species composition could also accumulate to affect total transpiration over longer (daily-seasonal-annual) time scales by affecting water use efficiency and the effective degree of daily stomata-closing stresses the trees experience post disturbance. By analyzing and understanding these fast daily dynamics rather than longer-term periods (monthly) or periods of drought stress, it may be possible to improve modeling of transpiration at the subdaily time step [Thompson et al, 2011] as well as to show more realistic coupling between hydrodynamic phenomena and gross primary productivity in land surface models [Fatichi and Ivanov, 2014].…”
Section: Introductionmentioning
confidence: 99%